Quantitative NMR analysis of Erk activity and inhibition by U0126 in a panel of patient-derived colorectal cancer cell lines - Rose, H; Stuiver, M; Thongwichian, R; Theillet, F; Feller, S; Selenko, P (2013)
We comparatively analyzed the basal activity of extra-cellular signal-regulated kinase (Erk1/2) in lysates of 10 human colorectal cancer cell lines by semi-quantitative Western blotting and time-resolved NMR spectroscopy. Both methods revealed heterogeneous levels of endogenous Erk1/2 activities in a highly consistent manner. Upon treatment with U0126, an inhibitor of mitogen-activated protein kinase kinase (MEK) acting upstream of Erk1/2, Western-blotting and NMR congruently reported specific modulations of cellular phospho-Erk levels that translated into reduced kinase activities. Results obtained in this study highlight the complementary nature of antibody- and NMR-based phospho-detection techniques. They further exemplify the usefulness of time-resolved NMR measurements in providing fast and quantitative readouts of kinase activities and kinase inhibitor efficacies in native cellular environments. This article is part of a Special Issue entitled: Inhibitors of Protein Kinases (2012). © 2013 Elsevier B.V.